Males of the genus Sericostoma Latreille 1825 in Turkey (Trichoptera, Sericostomatidae) - Si̇pahi̇ler Füsun (Zootaxa, 2021)
The males of the genus Sericostoma Latreille 1825 in Turkey were studied and the following new species are described and illustrated: Sericostoma dimcay sp. n., S. alakir sp. n., S. taskent sp. n., S. pinargozu sp. n., and S. yuvarlakcay sp. n. Sericostoma mesopotamicum McLachlan 1898 is accepted as a valid species, and a detailed description of the male of this species is given and illustrated. Sericostoma flavicorne Schneider 1845, S. grusiense Martynov 1913, and S. ida SİPAHİLER 2000 are also described and figured. The known species of the genus Sericostoma in Turkey have reached nine with the addition of these new species.